Public administration bodies competent in environmental protection in agriculture (requests and demands de lega lata and de lege ferenda) - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
Undertaking activities in agriculture associated with the implementation of environmental standards. This applies to Polish public administration and European Union bodies. A coherent policy for agricultural development will enable the financing of environmental protection in this area, both within the current budget, as well as the financial period 2014-2020.